Characterization of nickel manganite NTC thermistor films prepared by aerosol deposition at room temperature. Issue 2 (February 2018) - Schubert, Michaela; Münch, Christian; Schuurman, Sophie; Poulain, Véronique; Kita, Jaroslaw; Moos, Ralf
Abstract: NiMn2 O4+δ thermistor thick films have been successfully deposited by the so-called Aerosol Deposition Method (ADM) at room temperature on alumina substrates, Si-wafers, as well as on special planar four-wire interdigital electrode structures for high-precision electrical characterization. The NTCR films are homogeneous, completely dense and scratch resistant. Both as-deposited and tempered, the NTCR films exhibit a cubic spinel structure. Between 25 °C and 90 °C, the NTCR film resistance behaves as it is typical for variable range hopping (VRH) with parabolic density of states. As a result of moderate film tempering, the thermistor constant B and the specific resistance at 25 °C ( ρ 25 ) decrease from 4250 K to 4020 K and 65 Ω·m to 40 Ω·m respectively, and are close to bulk values. In combination with the excellent reproducibility of the ρ 25 and B values, AD processing of films appears to be a promising alternative for classical ceramic bulk processes.